2016
DOI: 10.1016/j.gaceta.2015.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Efectividad de un programa de juego basado en realidad virtual para la mejora cognitiva en la esquizofrenia

Abstract: Participation in virtual reality interventions aimed at cognitive training have great potential for significant gains in different cognitive domains assessed in patients with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 7 publications
1
23
0
3
Order By: Relevance
“…And it is consistent with the previous research which reported that 40 patients with schizophrenia got signi cantly improvement in MCCB domain of SP, AV, WM, VERL and RPS after 10 sessions of VR game program (32). The different MCCB domains improved in two studies might be related with different tasks in virtual situation.…”
Section: Discussionsupporting
confidence: 91%
“…And it is consistent with the previous research which reported that 40 patients with schizophrenia got signi cantly improvement in MCCB domain of SP, AV, WM, VERL and RPS after 10 sessions of VR game program (32). The different MCCB domains improved in two studies might be related with different tasks in virtual situation.…”
Section: Discussionsupporting
confidence: 91%
“…It is noteworthy that the theoretical framework used in NeuroVRehab.PT highly contrasts with the one used in CCTP and BTG. While, in CCTP and BTG, individual exercises are developed to target isolated cognitive functions [64][65][66], in our platform we focused on developing a training exercise that aims to stimulate/train the adequate behavioral patterns/responses to perform one specific IADL successfully. Therefore, in NeuroVRehab.PT we privileged activity segmentation into its basic units (e.g., creating a shopping list, searching for products, checking the shopping) as a means to promote the patient's awareness of where and how errors occur, along with the availability of simple strategies that patients could apply when shopping in the real world (e.g., organizing the shopping list and checking it before leaving each supermarket section).…”
Section: Discussionmentioning
confidence: 99%
“…Big Brain Academy game A virtual reality system and software using the Nintendo ® Wii video console [23]. Park et al (2011) sought to examine the utility of virtual reality (VR) in social rehabilitation and its role in skill formation.…”
Section: Vrvtsmentioning
confidence: 99%